Vibrant Architecture. Matter as a CoDesigner of Living Structures (2015)
This chapter speculatively explores how the principles of vibrant matter may be applied to an urban-scale project. Specifically, it proposes to empower the city of Venice with lifelike abilities that enable it to engage in a struggle for survival against the elements – just like living things do! ‘Vibrant Venice’ was initiated in February 2009, as a model system that proposed to couple the synthetic activity of artificial and natural systems within the lagoon to grow an artificial limestone reef under the city. The project is a multidisciplinary collaboration that combines speculative fiction, empirical science, fieldwork and architectural design. A particular kind of ELT was conceived for this project, based on dynamic oil droplets that are light sensitive and can produce an accretion material using resources in the lagoon system. The sinking of Venice into the soft delta soils on which it is founded is offset by the accretion of an artificial reef around the woodpiles, which spread the point load of the city over a much broader base. This project has been developed in collaboration with Neil Spiller and Martin Hanczyc, with drawings produced by working with Christian Kerrigan and GMJ. Vibrant Venice is not just a speculative proposition, but has been supported by field tests that are based on scientific research, which is at an early stage of development. The project proposes how vibrant matter may be applied through ELT across different scales of operation, and raises questions about how humans and non-humans may begin to codesign their environment and evolve their shared environmental future.